2019
DOI: 10.1186/s13014-019-1301-5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative elective pelvic nodal irradiation compared to prostate bed irradiation in locally advanced prostate cancer – a retrospective analysis of dose-escalated patients

Abstract: Background It is uncertain if whole-pelvic irradiation (WPRT) in addition to dose-escalated prostate bed irradiation (PBRT) improves biochemical progression-free survival (bPFS) after prostatectomy for locally advanced tumors. This study was initiated to analyze if WPRT is associated with bPFS in a patient cohort with dose-escalated (> 70 Gy) PBRT. Methods Patients with locally advanced, node-negative prostate carcinoma who had PBRT with or without WPRT after prostatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…There has been considerable controversy over whether to choose whole pelvic radiotherapy (WPRT) or prostate-only radiotherapy (PORT) for localized prostate cancer (37). This meta-analysis included six randomized controlled studies (RCTs) (7)(8)(9)(10)(11)(12) and ten cohort studies (CRS) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Of the 16 studies, 9 studies did not perform radical prostatectomy (non-RP), and the patients of the other 7 studies received radical prostatectomy (RP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been considerable controversy over whether to choose whole pelvic radiotherapy (WPRT) or prostate-only radiotherapy (PORT) for localized prostate cancer (37). This meta-analysis included six randomized controlled studies (RCTs) (7)(8)(9)(10)(11)(12) and ten cohort studies (CRS) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Of the 16 studies, 9 studies did not perform radical prostatectomy (non-RP), and the patients of the other 7 studies received radical prostatectomy (RP).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4,680 publications and 52 registered clinical studies were identified from the literature search, and 16 studies that met the eligibility criteria were finally selected, including 6 randomized controlled trials (RCTs) (7)(8)(9)(10)(11)(12) and 10 cohort studies (CRS) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Four studies that met the inclusion criteria were excluded because of no hazard ratio available for survival (33)(34)(35)(36).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation